Studi Literatur: Pengaruh Diet Mediterania terhadap Profil Lipid dan Glukosa Darah Puasa pada Orang Overweight atau Obesitas: Literature Review: The Effect of Mediterranean Diet on Lipid Profile and Fasting Blood Glucose in Overweight or Obese - Gustina Berta Uli; Sekar Ramadhanti Asyahir; Leny Budhi Harti (Amerta Nutrition, 2023)
Background: National Basic Health Research or Riset Kesehatan Dasar in 2018 stated that obesity in Indonesia had reached 21.8%. Being overweight and obese are among the risk factors that increase various health problems, including dyslipidemia and type 2 diabetes mellitus; hence, lifestyle changes are needed, one of which is through dietary modification. The Mediterranean diet is said to improve the lipid and glucose profiles of overweight or obese people.   Objectives: This literature study aimed to determine the effect of the Mediterranean diet on lipid profiles and blood glucose levels of overweight or obese people.  Methods: This research was conducted using the literature review method on two databases that consist of Pubmed and Cochrane, with specific keywords: "Mediterranean Diet," "Obese," "Overweight," "Lipid," dan "Glucose." The inclusion criteria in this study were articles that have been through peer review and proven that the articles are credible nationally and internationally. In addition, the literature was published in the last ten years, from 2012 to 2022, with RCT research design, using English or Indonesian, >18 years old subjects classified as obese or overweight, and can be accessed online. Meanwhile, the exclusion criteria for this study were literature using pregnant women as a subject, <18 years old subjects, and a non-RCT method study.  Discussion: Mediterranean diet is a type of diet that consumes foods high in monounsaturated fatty acid, polyunsaturated fatty acid, and soluble fiber. According to the results of this literature review, these nutrients improve lipid profiles in obese and overweight people. The Mediterranean diet's antioxidant composition and low glycemic index were also found to lower fasting blood glucose levels. In addition, carbohydrate control and physical activity are associated with fluctuation in insulin sensitivity that can affect fasting blood glucose levels in obese and overweight people.   Conclusions: It was found that some literature stated that the Mediterranean diet could lower the levels of LDL, triglycerides, and total cholesterol, increase HDL levels and lower fasting blood glucose levels.